Composite porous material of anticancer drug-containing liposome, photothermal conversion nanoparticle and bioabsorbable polymer and method for producing the same
Patent Information
- Application Number
- JP2022079877
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2022-05-16
- Publication Date
- 2025-04-03
- Estimated Expiration
- 2042-05-16
AI Technical Summary
Current cancer treatments, such as photothermal therapy and chemotherapy, face challenges in efficiently accumulating nanoparticles and anticancer drugs at cancer sites while minimizing side effects, leading to incomplete cancer cell eradication and recurrence.
A composite porous material containing bioabsorbable polymers, photothermal conversion nanoparticles, and liposomes encapsulating anticancer drugs is implanted at the cancer site or applied directly to cancer tissue, generating heat and releasing drugs in a controlled manner upon near-infrared irradiation.
The material efficiently kills cancer cells through localized heating and sustained drug release, reducing recurrence by ensuring complete cancer cell elimination with minimal impact on surrounding tissues.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical Field]
[0001] The present invention relates to a composite porous material and a method for producing the same, which is implanted in the site where cancerous tissue has been surgically removed, or which directly covers cancerous tissue, generates heat when irradiated with near-infrared light from outside the body, and releases an anticancer agent from the porous material, thereby killing cancer cells in or around the porous material through the heat generation and the sustained release of the anticancer agent, and treating cancer. [Background technology]
[0002] Cancer is the leading cause of death among all diseases, and even today, one in three people dies from cancer. With the progression of a super-aging society, the societal need for a fundamental treatment for cancer is extremely high. In order to eradicate cancer, various treatment methods and drugs have been actively developed. Surgical treatment, which is commonly used as a treatment for solid tumors, is the most direct method, in which the cancerous tissue is removed, and if there is metastasis to surrounding tissues or lymph nodes, those are also removed. Surgical treatment is actively performed even for early-stage or advanced cancers if it is resectable. One of the advantages of surgical treatment is that it allows for the removal of a mass of cancerous tissue in one go.
[0003] However, in reality, cancer recurs quite frequently even after surgery. This is because cancer cells and tiny cancerous tissues that cannot be detected by current imaging techniques remain in the body after surgery. The smaller the area removed in order to preserve the function of tissues and organs, the higher the possibility of leaving behind cancer cells and tissues, and thus the higher the risk of recurrence.
[0004] Therefore, a challenge in surgical treatment is how to treat any remaining cancer cells or microscopic cancerous tissue. Typically, chemotherapy or radiation therapy is often used in combination with surgery. In this way, multidisciplinary treatment, which combines multiple treatment methods, is employed in cancer treatment.
[0005] Cancer hyperthermia is a method of killing cancer cells by heating them, taking advantage of the fact that cancer cells are more sensitive to heat than normal cells. Photothermal therapy, which involves incorporating nanoparticles that generate heat when they absorb near-infrared light (photothermal conversion nanoparticles) into cancer tissue and then irradiating the affected area with near-infrared light to kill cancer cells, is attracting attention. In photothermal therapy, when near-infrared light is irradiated onto the affected area from the outside, the photon energy absorbed by the photothermal conversion nanoparticles is converted into thermal energy. At this time, the temperature rises due to this thermal energy, and as a result, cancer cells die. Gold nanoparticles and black phosphorus nanosheets that generate heat when irradiated with near-infrared light are attracting attention. Gold nanoparticles and black phosphorus nanosheets have low toxicity to living cells, and in small amounts, they do not cause adverse effects on the body.
[0006] Previously, photothermal nanoparticles were administered systemically via injection or intravenous infusion, allowing them to accumulate in cancer tissue through the bloodstream. However, because they circulate throughout the body via the bloodstream, the accumulation efficiency in cancer tissue is low, leading to decreased treatment efficiency and the risk of side effects. The challenge with these treatments is how to efficiently accumulate a sufficient amount of nanoparticles in cancer cells while minimizing side effects.
[0007] Therefore, a method has been proposed in which photothermal conversion nanoparticles are compounded with a porous material and transplanted after surgical removal of large cancerous tissue, or by directly covering the cancerous tissue, thereby efficiently killing cancer cells by irradiation with near-infrared light from outside the body (see, for example, Patent Document 1 and Non-Patent Document 1). Since this material can be molded into any shape, it can be implanted in various locations within the body. Furthermore, because it is porous, it can efficiently take up cells scattered at the implantation site.
[0008] In chemotherapy, cancer is treated by suppressing or killing the growth of cancer cells with anticancer drugs. However, not only cancer cells but also normal tissue cells have side effects such as toxicity. How to efficiently accumulate a sufficient amount of anticancer drugs in cancer cells while suppressing side effects is an issue for these treatment methods. If the anticancer drug is introduced into a porous material that can be implanted and directly transplanted to the resection site during surgery or directly coated on the cancer tissue, it is considered that the anticancer drug can be efficiently delivered to cancer cells.
[0009] From the current situation of the above prior art, in order to remove cancer tissue by surgery and kill the remaining cancer cells, usually, chemotherapy with anticancer drugs is often combined after surgery. However, when the anticancer drug is administered systemically by injection or infusion, the anticancer drug is taken up not only by cancer cells but also by normal cells through the bloodstream, so the side effects are large. In addition, there is photothermal therapy in which photothermal conversion nanoparticles such as gold nanoparticles and black phosphorus nanosheets are administered systemically by injection or infusion as in Patent Document 1 and Non-Patent Document 1, and the nanoparticles are accumulated in cancer tissue through the bloodstream. However, it is difficult to ensure a sufficient accumulation amount of nanoparticles to kill cancer cells.
Prior Art Documents
Patent Documents
[0010]
Patent Document 1
Non-Patent Documents
[0011]
Non-Patent Document 1
Summary of the Invention
Problems to be Solved by the Invention
[0012] In view of these circumstances, the present invention aims to provide a composite porous material that is transplanted after surgical removal of cancerous tissue, or directly covered with cancerous tissue, and that generates heat and slowly releases an anticancer agent upon irradiation with near-infrared light, as well as a method for producing the same. [Means for solving the problem]
[0013] The composite porous material according to the present invention contains a bioabsorbable polymer, photothermal conversion nanoparticles that generate heat upon irradiation with near-infrared light, and liposomes containing an anticancer drug, thereby solving the above-mentioned problems. The photothermal conversion nanoparticles may be selected from the group consisting of gold nanoparticles and black phosphorus nanosheets, with at least one selected from this group. The gold nanoparticles may be in the form of rod-shaped gold nanorods or star-shaped gold nanostars. The gold nanorod may have a major axis length in the range of 20 nm to 500 nm, a minor axis length in the range of 1 nm to 80 nm, and an aspect ratio (major axis length / minor axis length) in the range of 2 to 50, and the grain diameter of the gold nanostar may be in the range of 20 nm to 500 nm. The black phosphorus nanosheet has a thickness in the range of 1 nm to 1,000 nm and an area of 100 nm. 2 ~100,000 μm 2 It may also be within that range. The anticancer agent is released slowly from the liposome by body temperature, and the release rate may be increased by the heat generated by the photothermal conversion nanoparticles. The aforementioned anticancer agent may be selected from one or more of the group consisting of doxorubicin, paclitaxel, docetaxel hydrate, methotrexate, fluorouracil, tegafur, tegafur-uracil, carmofur, doxifluridine, capecitabine, tegafur-gimeracil-oteracil potassium, mitomycin C, captothecin, and cisplatin. The liposomes may be composed of 1,2-dihexadecanoyl-sn-glycero-3-phosphocholine (abbreviated as DPPC), cholesterol, and 1,2-distearoyl-sn-glycero-3-phosphoethanolamine (abbreviated as DSPE) modified with polyethylene glycol. The bioabsorbable polymer may be selected from one or more types from the group consisting of gelatin, collagen, fibrin, hyaluronic acid, polyglutamic acid, chondroitin sulfate, alginic acid, polylactic acid, polyglycolic acid, copolymers of lactic acid and glycolic acid, poly(ε-caprolactone), poly(glycerol sebaciate), and copolymers thereof. The bioabsorbable polymer may be a bioabsorbable synthetic polymer sponge or a bioabsorbable synthetic polymer mesh. The bioabsorbable synthetic polymer mesh may be a woven fabric, a nonwoven fabric, or a textile. The material may have pores with a diameter in the range of 0.1 to 1200 μm. The bioabsorbable polymer may be crosslinked. The concentration of the aforementioned photothermal conversion nanoparticles is 1 μg / cm³. 3 More than 4,000μg / cm 3 The following range is also acceptable. The weight ratio of the photothermal conversion nanoparticles to the bioabsorbable polymer (photothermal conversion nanoparticles / bioabsorbable polymer) may be in the range of 0.0005 to 0.5. The final concentration of the anticancer drug released by the liposomes is 0.01 mg / cm³. 3 More than 100mg / cm 3 The following range is also acceptable. It may be implanted in the area where cancerous tissue has been removed by surgical removal, or it may directly cover the cancerous tissue and generate heat when irradiated with near-infrared light from the outside, killing internal or surrounding cancer cells. The method for producing the composite porous material according to the present invention includes mixing photothermal conversion nanoparticles and a bioabsorbable polymer to create a porous material, and introducing liposomes containing an anticancer agent into the porous material of the photothermal conversion nanoparticles and the bioabsorbable polymer obtained by the porous material creation, thereby solving the above problem. The process of creating a porous structure may include freeze-drying the mixed solution of the photothermal conversion nanoparticles and the bioabsorbable polymer. The aforementioned process of creating porosity may include using a pore-forming agent to create pores. The pore-forming agent may be ice. The process may further include crosslinking the porous material following the aforementioned porous formation. The liposomes containing the anticancer drug may be prepared by a method selected from the group consisting of the Bangham method, cholic acid removal method, reverse-phase evaporation method, microreactor method, remote loading method, and freeze-thaw method. The aforementioned introduction may include chemically bonding the liposomes containing the anticancer drug to the porous material. [Effects of the Invention]
[0014] This invention allows for the controlled release of anticancer drugs by transplanting a composite porous material to the excision site of cancerous tissue or by covering the cancerous tissue with the composite porous material, thereby clearly localizing the heating of only a region of any shape. Furthermore, the amount of heat generated and the amount of anticancer drug released at each location can be adjusted by varying the amount of composite porous material sample (thickness, size, etc.) and the content of photothermal conversion nanoparticles and anticancer drugs in the material used at each location. Therefore, cancer cells can be efficiently killed even when cancerous tissue is located in a region with a complex shape or near a site where thermal damage would cause serious harm. In addition, the porous structure allows cancer cells to penetrate into the composite porous material, enabling efficient killing of cancer cells. Moreover, because the nanoparticles are supported on the porous material, rapid diffusion of the nanoparticles, which reduces the photothermal conversion efficiency, is prevented, making it possible to repeatedly heat the excision site or cancerous tissue locally. Furthermore, heating can also promote the controlled release of anticancer drugs by increasing the permeability of the lipid membrane of liposomes. Therefore, by irradiating with near-infrared light, it is possible to repeatedly heat cancer tissue and cancer cells, and to kill them through the sustained release of anticancer drugs. [Brief explanation of the drawing]
[0015] [Figure 1]This figure shows a transmission electron microscope image of the fabricated photothermal conversion nanoparticles, which are gold nanorods. [Figure 2] This figure shows the dynamic light scattering grain distribution of liposomes containing the prepared doxorubicin. [Figure 3] Figure showing SEM observation of the interior of the composite porous material in Example 1. [Figure 4] Figure showing SEM observation of the interior of the composite porous material of Comparative Example 1. [Figure 5] Figure showing SEM observation of the interior of the composite porous material of Comparative Example 2. [Figure 6] This figure shows the temperature change when the composite porous material of Example 1 is irradiated with near-infrared light. [Figure 7] This figure shows the temperature change when near-infrared light is irradiated onto the composite porous material of Comparative Example 1. [Figure 8] This figure shows the temperature change when near-infrared light is irradiated onto the composite porous material of Comparative Example 2. [Figure 9] This figure shows the accumulation and sustained release curve of doxorubicin when the composite porous material of Example 1 is irradiated with near-infrared light. [Figure 10] This figure shows a fluorescence micrograph of the composite porous material from Example 1, in which human cancer cell lines were cultured after infrared light irradiation (cultivated for 1 day). [Figure 11] This figure shows a fluorescence micrograph of the composite porous material of Comparative Example 1, in which human cancer cell lines were cultured after infrared light irradiation (1 day of culture). [Figure 12] This figure shows a fluorescence micrograph of the composite porous material of Comparative Example 2, in which human cancer cell lines were cultured after infrared light irradiation (cultivated for 1 day). [Figure 13] This figure shows the cell viability in composite porous materials of Example 1 and Comparative Examples 1-2, in which human cancer cell lines were cultured after infrared light irradiation (cultured for 1 day). [Figure 14] This figure shows the cell viability in composite porous materials of Example 1 and Comparative Examples 1-2, in which human cancer cell lines were cultured after infrared light irradiation (3-day culture). [Figure 15] This figure shows an in vivo chemiluminescence image of mice transplanted with the composite porous material from Example 1, in which human cancer cell lines were cultured after infrared light irradiation. [Figure 16]This figure shows an in vivo chemiluminescence image of mice transplanted with the composite porous material of Comparative Example 1, which was cultured using a human cancer cell line after infrared light irradiation. [Figure 17] This figure shows an in vivo chemiluminescence image of mice transplanted with the composite porous material from Comparative Example 2, which was cultured using human cancer cell lines after infrared light irradiation. [Modes for carrying out the invention]
[0016] The following description of the constituent elements may be based on typical embodiments of the present invention, but the present invention is not limited to such embodiments. In this specification, a numerical range represented by "~" means a range that includes the numbers written before and after "~" as the lower and upper limits, respectively.
[0017] The composite porous material of the present invention contains a bioabsorbable polymer, photothermal conversion nanoparticles that generate heat upon near-infrared light irradiation, and liposomes containing an anticancer drug. Since the photothermal conversion nanoparticles generate heat upon near-infrared light irradiation, the composite porous material can be used to locally heat and kill cancerous tissue by transplanting it to the excision site or covering the cancerous tissue. Furthermore, the liposomes containing the anticancer drug slowly release the drug at body temperature, and the rate of release increases as the temperature rises. Therefore, by transplanting the composite porous material to the excision site or covering the cancerous tissue, the cancerous tissue can be killed with the anticancer drug. Each constituent element will be described in detail below.
[0018] The bioabsorbable polymer may be one or more selected from the group consisting of gelatin, collagen, fibrin, hyaluronic acid, polyglutamic acid, chondroitin sulfate, alginic acid, polylactic acid, polyglycolic acid, copolymers of lactic acid and glycolic acid, poly(ε-caprolactone), poly(glycerol sebaciate), and copolymers thereof. The bioabsorbable polymer may be crosslinked. This stabilizes the porous structure. Crosslinking is particularly preferable when using water-soluble bioabsorbable polymers such as gelatin and collagen, but it is not necessarily required when using water-insoluble bioabsorbable polymers such as polylactic acid and polyglycolic acid.
[0019] The bioabsorbable polymers preferably used in the present invention are polymers selected from one or more types from gelatin, polyglutamic acid, collagen, hyaluronic acid, and alginic acid. Twenty-nine types of collagen are known, including types I, II, III, IV, V, VI, VII, VIII, IX, and X, and any of these can be used in the present invention, as well as derivatives thereof. The bioabsorbable polymer may be in the form of a mesh (bioabsorbable synthetic polymer mesh) or a sponge (bioabsorbable synthetic polymer sponge). This increases the mechanical strength of the porous material, facilitates handling, and makes implantation easier. The mesh may be a woven fabric, a nonwoven fabric, or a textile.
[0020] The bioabsorbable polymer may consist of one or more types of bioabsorbable polymers, including one modified with a ligand that recognizes cancer cells and one or more unmodified bioabsorbable polymers. One or more of the ligands that recognize cancer cells, such as folic acid, RGD peptide, and membrane-permeable peptides, may be used in combination. The bioabsorbable polymer is modified by chemical bonding with the ligand that recognizes cancer cells.
[0021] The above-mentioned ligand-modified bioabsorbable polymer is synthesized by binding a bioabsorbable polymer with a cancer-recognizing ligand. Any conventionally known method can be used to bind the bioabsorbable polymer with the cancer-recognizing ligand. Generally, a condensing agent that catalyzes the binding is used. Any conventionally known condensing agent can be used. Preferably used condensing agents include one or more aldehydes such as N,N'-dicyclohexylcarbodiimide (abbreviated as DCC), N-hydroxysuccinimide (abbreviated as NHS), 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride, glutaraldehyde, formaldehyde, and paraformaldehyde.
[0022] The photothermal conversion nanoparticles are not particularly limited as long as they generate heat upon irradiation with near-infrared light (wavelength: 780 nm to 2.5 μm), but preferably, at least one is selected from the group consisting of gold nanoparticles and black phosphorus nanosheets. These have been confirmed to generate heat in living organisms upon irradiation with near-infrared light. Gold nanoparticles and black phosphorus nanosheets can be used, for example, those shown in Patent Document 1 and Non-Patent Document 1, but commercially available gold nanoparticles and black phosphorus nanosheets may also be used.
[0023] For example, gold nanoparticles may be synthesized according to previously reported methods (J. Li et al., Nanoscale, 8, 7992-8007 (2016)). By synthesizing using the method described above, gold nanoparticles of different sizes (e.g., approximately 35.0 nm, 65.0 nm, and 115.0 nm) and shapes (e.g., rod-shaped and star-shaped) can be obtained.
[0024] For example, black phosphorus nanosheets can be prepared by sonicating bulk black phosphorus in a solvent (wet exfoliation method), or they can be synthesized by electrochemical methods as previously reported (Jing Li et al., Chemistry of Materials, 30, 2742-2749 (2018)).
[0025] In addition to the shapes described above, the gold nanoparticles may have shapes such as spherical, sea urchin-like, spindle-shaped, triangular prism, cuboid, cube, etc., but preferably, they are rod-shaped gold nanorods or star-shaped gold nanostars.
[0026] For the gold nanorods, those with the length of the long axis (long axis length) in the range of 10 nm to 800 nm, the length of the short axis (short axis length) in the range of 0.5 nm to 100 nm, and the aspect ratio (length of the long axis / length of the short axis) in the range of 1.5 to 60 can be used. Considering the photothermal conversion efficiency, preferably, the length of the long axis is in the range of 20 nm to 500 nm, the length of the short axis is in the range of 1 nm to 80 nm, and the aspect ratio is in the range of 2 to 50. More preferably, the length of the long axis is in the range of 50 nm to 100 nm, the length of the short axis is in the range of 5 nm to 20 nm, and the aspect ratio is in the range of 2 to 10.
[0027] For the gold nanostars, those with a particle size in the range of 10 nm to 800 nm can be used. Considering the photothermal conversion efficiency, preferably, they have a particle size in the range of 20 nm to 500 nm. In the present specification, the particle size of the gold nanostar is the straight-line distance between the vertices of the outermost spines of the star shape.
[0028] The black phosphorus nanosheet can have a thickness in the range of 0.1 nm to 1,000 nm and an area in the range of 10 nm 2 ~1 mm 2 but considering the photothermal conversion efficiency, preferably, the thickness is in the range of 1 nm to 1,000 nm and the area is in the range of 100 nm 2 ~100,000 μm 2 is used.
[0029] Photothermal conversion nanoparticles can be used either with or without surface modification. The purpose of surface modification of photothermal conversion nanoparticles is to enhance their interaction with cancer cells. When cancer cells invade a composite porous material, they recognize the ligands modified on the surface of the photothermal conversion nanoparticles, making it easier for them to adhere to the nanoparticles and potentially kill them through the heat-generating effect. Furthermore, when the composite porous material decomposes, the released photothermal conversion nanoparticles are recognized by cancer cells, making it easier for them to take up the nanoparticles and more efficiently kill the cancer cells.
[0030] For surface modification, it is possible to use one or more ligands from the group consisting of folic acid, RGD peptide, and membrane-permeable peptides, which are ligands recognized by cancer cells.
[0031] The concentration of photothermal conversion nanoparticles in the composite porous material of the present invention is preferably 1 μg / cm³. 3 More than 4,000μg / cm 3 The range is as follows: 1 μg / cm³ 3 If the concentration is below 4,000 μg / cm³, the heat generated by near-infrared light irradiation may not be sufficient, and the cancer cell killing effect may not be adequately achieved. 3 Beyond a certain level, the photothermal conversion nanoparticles may aggregate. Within this range, a composite porous material can be provided that efficiently kills cancer cells through the exothermic effect of low concentrations of photothermal conversion nanoparticles. For example, the concentration of photothermal conversion nanoparticles is 100 μg / cm³. 3 More than 600μg / cm 3 The following ranges can be adopted. The concentration of the photothermal conversion nanoparticles may also be estimated by the final concentration of photothermal conversion nanoparticles in the porous material raw material solution during manufacturing. For example, the concentration of the photothermal conversion nanoparticles can be in the range of 0.005 mM or more and 20 mM or less.
[0032] The weight ratio (photothermal conversion nanoparticles / bioabsorbable polymer) of the photothermal conversion nanoparticles in the composite porous material of the present invention is preferably in the range of 0.0005 to 0.5 in the photothermal conversion nanoparticle / bioabsorbable polymer mixed solution used in the preparation of the porous material. If the proportion of bioabsorbable polymer is too low, it may be difficult to support all of the photothermal conversion nanoparticles in the porous material. If the proportion of bioabsorbable polymer is too high, sufficient heating efficiency due to the photothermal effect may not be obtained. The weight ratio is more preferably in the range of 0.001 to 0.3. Since it is difficult to determine the weight ratio of photothermal conversion nanoparticles to bioabsorbable polymer in the composite porous material with high precision, it is simply considered to be synonymous with the weight of the photothermal conversion nanoparticles in the photothermal conversion nanoparticle / bioabsorbable polymer mixed solution used in the preparation of the composite porous material. For example, a weight ratio (photothermal conversion nanoparticles / bioabsorbable polymer) of 0.005 to 0.015 can be adopted.
[0033] Anticancer drug-encapsulated liposomes (anticancer drug-encapsulated liposomes) are formulations in which anticancer drugs are encapsulated within liposomes, which are organic substances that are components of cell membranes and biological membranes, and are known as drug delivery systems. The particle size of the anticancer drug-encapsulated liposomes is preferably in the range of 100 nm to 500 nm. Within this range, the anticancer drug-encapsulated liposomes and photothermal conversion nanoparticles can be uniformly dispersed. The particle size of the anticancer drug-encapsulated liposomes is preferably in the range of 150 nm to 300 nm. The particle size of the anticancer drug-encapsulated liposomes can be measured using a dynamic light scattering measurement device.
[0034] The anticancer agents preferably used in the present invention are one or more selected from the group consisting of doxorubicin, paclitaxel, docetaxel hydrate, methotrexate, fluorouracil, tegafur, tegafur-uracil, carmofur, doxifluridine, capecitabine, tegafur-gimeracil-oteracil potassium, mitomycin C, captothecin, and cisplatin. The anticancer agents are released from liposomes at body temperature, and the rate of release is further increased by the heat generated by photothermal conversion nanoparticles.
[0035] The concentration of the anticancer drug encapsulated in the liposomes, i.e., the final concentration of the anticancer drug released by the liposomes, is preferably 0.01 mg / cm³. 3 More than 100mg / cm 3 The following ranges apply. If the concentration of the anticancer drug is too low, it may not be able to kill cancer cells and tissues. If the concentration of the anticancer drug is too high, it may adversely affect normal cells and tissues, and side effects may become more severe. However, since the composite porous material of the present invention allows for local administration, 100 mg / cm³ is possible. 3 It can be administered even at high concentrations up to 0.7 mg / cm³. The concentration of the anticancer drug may also be estimated by the final concentration of the anticancer drug relative to the volume of the porous material at the time of manufacture. For example, the concentration of the anticancer drug is 0.7 mg / cm³. 3 More than 1.3mg / cm 3 The following ranges can be adopted.
[0036] In the present invention, the liposomes preferably used as liposomes encapsulating anticancer drugs are liposomes composed of 1,2-dihexadecanoyl-sn-glycero-3-phosphocholine (abbreviated as DPPC), cholesterol, and 1,2-distearoyl-sn-glycero-3-phosphoethanolamine (DSPE) modified with polyethylene glycol. The molar ratio of DPPC, cholesterol, and polyethylene glycol-modified DSPE is in the range of 6-9:3-1:2-0.5. The preferred molar ratio of DPPC, cholesterol, and polyethylene glycol-modified DSPE is 7:2:1.
[0037] Anticancer drug-encapsulated liposomes may be obtained commercially, or they may be synthesized using methods such as the Bangham method, cholic acid removal method, reverse-phase evaporation method, microreactor method, remote loading method, or freeze-thaw method.
[0038] The composite porous material of the present invention can be cut into the required shape depending on the transplant site. The length and width dimensions can be determined as appropriate, but usually each side is 1 to 200 mm, preferably 2 to 150 mm. The thickness is 0.1 to 100 mm, preferably 0.2 to 50 mm. The pore size of the composite porous material is preferably 0.1 to 1200 μm, preferably 1 to 1000 μm. The porosity is usually 5 to 99.9%, preferably 20 to 99.5%.
[0039] In this specification, the pore size was measured using electron microscope (SEM) images and image analysis as described in Qin Zhang et al., Acta Biomaterialia 10 (2014) 2005. Furthermore, the porosity can be calculated as described in the examples.
[0040] To increase the mechanical strength of the composite porous material, it may be reinforced with a bioabsorbable structural material. The bioabsorbable structural material may be one or more mesh bodies or sponge bodies selected from the group consisting of polylactic acid, polyglycolic acid, copolymers of lactic acid and glycolic acid, poly(ε-caprolactone), poly(glycerol sebacic acid), and copolymers thereof.
[0041] The ligand for modifying the surface of the above photothermal conversion nanoparticles may be directly bound to the surface of the nanoparticles, or a ligand-modified bioabsorbable polymer in which the above bioabsorbable polymer and ligand are bound may be used.
[0042] Next, an exemplary method for manufacturing the composite porous material of the present invention will be described. The composite porous material of the present invention comprises the steps of mixing photothermal conversion nanoparticles and a bioabsorbable polymer to create a porous material (porosity creation step), and introducing liposomes containing an anticancer drug into the porous material of photothermal conversion nanoparticles and a bioabsorbable polymer obtained by porosity creation (introduction step). Each step will be described in detail.
[0043] In the porous formation process, first, photothermal conversion nanoparticles are added to a solution of bioabsorbable polymer, and then the photothermal conversion nanoparticles are thoroughly dispersed in the bioabsorbable polymer solution by ultrasonic or mechanical stirring. The dispersion obtained in this way can be used as a porous material raw material solution to produce a porous material of photothermal conversion nanoparticles and bioabsorbable polymer. Here, the photothermal conversion nanoparticles and bioabsorbable polymer are as described above, and may or may not be surface modified.
[0044] Solvents for dissolving bioabsorbable polymers include pure water, a mixture of pure water and ethanol, aqueous acetic acid, dilute hydrochloric acid, an acetic acid / water / ethanol mixture, a hydrochloric acid / ethanol mixture, chloroform, carbon tetrachloride, dioxane, trichloroacetic acid, dimethylformamide, methylene chloride, ethyl acetate, acetone, hexafluoroisopropanol, dimethylacetamide, and hexafluoro-2-propanol. Preferred solvents are selected from the group consisting of pure water, a mixture of pure water and ethanol, aqueous acetic acid, dilute hydrochloric acid, an acetic acid / water / ethanol mixture, and a hydrochloric acid / ethanol mixture. The pH of the pH-adjusted solution is 1 to 6.8, with a preferred pH of 2.5 to 6. The volume ratio of ethanol to water can be 1:99 to 50:50, but is preferably 1:99 to 20:80.
[0045] Here, the final concentration of the bioabsorbable polymer in the porous material raw material solution can be any concentration as long as the bioabsorbable polymer is dissolved in the solvent, but it is preferably prepared to be between 0.1(w / v)% and 40(w / v)%. If it is less than 0.1(w / v)%, the mechanical strength of the resulting composite porous material may not be sufficient, and it may not be able to maintain the predetermined shape. If it exceeds 40(w / v)%, the porosity of the resulting composite porous material will decrease significantly, and the diffusibility of nutrients supplied to cells and waste products discharged by cells may decrease. The final concentration of the bioabsorbable polymer is more preferably between 0.2(w / v)% and 30(w / v)%. The bioabsorbable polymer used is as described above, so its explanation is omitted.
[0046] When preparing a solution of a bioabsorbable polymer, the preparation should be carried out at a temperature that does not cause the polymer to decompose or gel. This is usually between 1 and 60°C, but preferably between 4 and 50°C.
[0047] Methods for creating a porous material include, for example, freeze-drying a mixed solution of photothermal conversion nanoparticles and bioabsorbable polymers (porous material raw material solution) as is, and forming pores in a mixed solution of photothermal conversion nanoparticles and bioabsorbable polymers using a pore-forming agent. Ice (ice particles) can be used as the pore-forming agent.
[0048] In the direct freeze-drying method, the pore size and shape depend on the freezing rate and freezing temperature. In the method using pre-prepared ice microparticles, the pore size and shape depend on the size and shape of the ice microparticles.
[0049] The freeze-drying method is described below. In the method of freeze-drying a mixed solution of photothermal-converting nanoparticles and bioabsorbable polymers as is, the mixed solution of photothermal-converting nanoparticles and bioabsorbable polymers is pre-frozen. For example, photothermal-converting nanoparticles are added to a solution of bioabsorbable polymers, and the photothermal-converting nanoparticles are thoroughly dispersed in the bioabsorbable polymer using ultrasound or mechanical stirring. The mixed solution consisting of the uniformly dispersed photothermal-converting nanoparticles and bioabsorbable polymers is left to stand in a freezer for several hours to freeze. The freezer temperature is -1 to -100°C, with a desirable temperature of -5 to -80°C. The freezing time is 1 to 24 hours, with a desirable freezing time of 2 to 8 hours.
[0050] A method using a pore-forming agent will be described. First, pure water is sprayed into liquid nitrogen to produce ice particles. The formed ice particles are transferred in a container to a low-temperature chamber (-15°C), and the container is left to stand until the liquid nitrogen inside the container vaporizes and disappears. Then, ice particles of a predetermined particle size are sieved using a sieve with a large mesh size and a sieve with a small mesh size. The mesh size of each sieve is nominally 1 to 1,000 μm, preferably nominally 10 to 800 μm. The sieved ice particles are left to stand in a low-temperature chamber at -4°C for 1 to 6 hours to equilibrium the temperature of the ice particles at -4°C. Then, a mixed solution consisting of the photothermal conversion nanoparticles and bioabsorbable polymer is transferred to a low-temperature chamber at -4°C and left to stand for several tens of minutes to equilibrium the temperature. A mixed solution consisting of photothermal conversion nanoparticles and bioabsorbable polymers, heated to -4°C, and sieved ice particles, also heated to -4°C, are mixed in a 4°C low-temperature chamber at a fixed volume mL to weight g ratio. The ratio of the mixed solution of photothermal conversion nanoparticles and bioabsorbable polymers to the ice particles can be 99:1 to 10:90 in volume mL to weight g, but a desirable ratio (volume mL to weight g) is 80:20 to 30:70. The mixture is thoroughly stirred so that the ice particles are uniformly dispersed in the mixed solution of photothermal conversion nanoparticles and bioabsorbable polymers. The mixture is left to stand at -20°C for 12 hours, and then frozen by leaving it to stand at -80°C for another 4 hours.
[0051] In both of the above methods, the frozen material prepared during the process is freeze-dried at room temperature under reduced pressure of 5 Pa or less for 3 days to form a porous material of photothermal conversion nanoparticles and bioabsorbable polymers.
[0052] Following the porous formation process, the resulting photothermal conversion nanoparticles and the porous material of the bioabsorbable polymer may be crosslinked. This stabilizes the structure of the porous material. Crosslinking is particularly preferable when using water-soluble bioabsorbable polymers such as gelatin and collagen, but it is not necessarily required when using water-insoluble bioabsorbable polymers such as polylactic acid and polyglycolic acid.
[0053] Any conventionally known crosslinking method can be used. Generally, the steam method or the solution method can be used. Any conventionally known crosslinking agent can be used in the steam method. Preferably used crosslinking agents are aldehydes such as glutaraldehyde, formaldehyde, and paraformaldehyde, with glutaraldehyde being particularly preferred.
[0054] In the aforementioned vapor method (gas phase method), it is preferable to use the above-mentioned crosslinking agent in gaseous form. Specifically, a porous material of photothermal conversion nanoparticles and bioabsorbable polymer is crosslinked for a certain period of time under an atmosphere of crosslinking agent vapor saturated with a certain concentration of crosslinking agent or an aqueous solution thereof at a certain temperature. The crosslinking temperature should be within a range in which the porous material of photothermal conversion nanoparticles and bioabsorbable polymer does not dissolve and crosslinking agent vapor can be formed, and is usually set to 20 to 50°C. The crosslinking time depends on the type of crosslinking agent and the crosslinking temperature, but it is desirable to perform the crosslinking within a range in which crosslinking is immobilized without inhibiting the bioabsorbability of the porous material of photothermal conversion nanoparticles and bioabsorbable polymer, and without dissolving when implanted in a living organism. A preferred crosslinking time is about 10 minutes to 12 hours. After the crosslinking reaction, the porous material of photothermal conversion nanoparticles and bioabsorbable polymer is washed by immersion in pure water at room temperature, and this is repeated four or more times as one washing cycle.
[0055] In the solution crosslinking method, crosslinking is performed using a crosslinking agent such as carbodiimide, aldehydes, or epoxys, and an activator such as N-hydroxysuccinimide. Since the porous material of uncrosslinked photothermal conversion nanoparticles and bioabsorbable polymers dissolves in water, these crosslinking agents are dissolved in a mixed solvent of ethanol and water, and crosslinking is performed in several steps. The ratio of ethanol to water in the mixed solvent differs in each step, changing from a higher ratio to a lower ratio from the first to the final step. The ethanol / water ratio is between 1 / 99 and 99 / 1. The crosslinking temperature is 4 to 40°C, preferably room temperature. The concentration of the crosslinking agent is 5 to 500 mM, preferably 10 to 100 mM. The concentration of the activator is 5 to 500 mM, preferably 10 to 100 mM. The porous material of photothermal conversion nanoparticles and bioabsorbable polymers after the final crosslinking reaction is washed by immersion in pure water at room temperature, and this is repeated at least four times as one washing cycle.
[0056] In the introduction process, the anticancer drug-encapsulated liposomes are chemically bonded to a porous material composed of photothermal-converting nanoparticles and a bioabsorbable polymer. Preferably, this bonding occurs through a condensation reaction between the carboxyl groups of the porous material composed of photothermal-converting nanoparticles and the bioabsorbable polymer and the amino groups on the lipid membrane surface of the anticancer drug-encapsulated liposomes.
[0057] The condensation reaction is carried out, for example, as follows: A porous material consisting of photothermal conversion nanoparticles and a bioabsorbable polymer is activated by activating the carboxyl groups on its surface with 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, N-hydroxysuccinimide, etc. Then, it is mixed with anticancer drug-encapsulated liposomes, shaken, and incubated for a predetermined time. Heating may be applied to accelerate the reaction.
[0058] Prior to the introduction process, a step of encapsulating the anticancer drug in liposomes may be performed. Methods for producing anticancer drug-encapsulated liposomes include the Bangham method, cholic acid removal method, reverse-phase evaporation method, microreactor method, remote loading method, and freeze-thaw method, as described above. The preferred method is the Bangham method, in which an aqueous solution of the anticancer drug is added to a thin lipid film and hydrated, causing the lipids to self-assemble and form liposomes encapsulating the anticancer drug.
[0059] After the introduction process, the porous material into which the anticancer drug-encapsulated liposomes have been introduced may be washed and freeze-dried. Specifically, the porous material is washed with pure water for 30 minutes at least three times. After washing, freeze-drying is performed under reduced pressure of 5 Pa or less for 48 hours to obtain a composite porous material of the target anticancer drug-containing liposomes, photothermal conversion nanoparticles, and bioabsorbable polymer.
[0060] Although we have explained that crosslinking of the bioabsorbable polymer is performed after the porous process and before the introduction process, crosslinking may also be performed after the introduction process. The conditions in this case are as described above.
[0061] As described above, the composite porous material of the present invention containing anticancer drug-containing liposomes, photothermal conversion nanoparticles, and bioabsorbable polymers is obtained. When the composite porous material of the present invention is irradiated with near-infrared light from the outside, the photothermal conversion nanoparticles generate heat, which can kill cancer cells and cancer tissue. By repeatedly irradiating with near-infrared light as needed and repeatedly generating heat in the photothermal conversion nanoparticles, it is expected that the killing effect on cancer cells and cancer tissue can be enhanced. Furthermore, the anticancer drug can be released slowly from the anticancer drug liposomes introduced into the composite porous material. In addition, the rate of slow release of the anticancer drug from the anticancer drug liposomes can be increased by the heat generation, and the slow release of the anticancer drug can be controlled by near-infrared light irradiation. This is expected to efficiently kill cancer tissue and cancer cells. Moreover, such a composite porous material can raise the temperature of the inside of the composite or the surrounding area to a temperature suitable for hyperthermia therapy and maintain that temperature for a desired time without the need for external electrical wiring or piping to supply heating fluids. Furthermore, the composite porous material according to the present invention can efficiently take surrounding cells into its pores and heat them. Therefore, for example, it is possible to capture and kill cancer cells that remain near the excision site after surgery.
[0062] The present invention will now be described in detail using specific examples, but please note that the present invention is not limited to these examples. [Examples]
[0063] [Preparation of raw materials] <Surface-modified gold nanorods> As photothermal conversion nanoparticles, gold nanorods surface-modified with folic acid (folic acid-modified gold nanorods) were prepared.
[0064] Gold nanorods were synthesized using the seed growth method. In the presence of cetyltrimethylammonium bromide (abbreviated as CTAB), tetrachloroauric acid (HAuCl4) was rapidly reduced from sodium borohydride (NaBH4) to produce CTAB-stabilized Au seeds. 10 mL of 0.01 M HAuCl4, 4 mL of 1 M HCl, 1.6 mL of 0.1 M ascorbic acid, 2.20 mL of 10 mM AgNO3, and 150 mL of 0.1 MCTAB were mixed to prepare the growth solution. While slowly stirring the growth solution, 0.48 mL of the Au seed solution was added, and the mixture was incubated for 12 hours to synthesize gold nanorods. The gold nanorods were then recovered by centrifugation and washed with Milli-Q water. The synthesized gold nanorods were observed using a transmission electron microscope.
[0065] Figure 1 shows a transmission electron microscope image of the fabricated photothermal conversion nanoparticles, which are gold nanorods.
[0066] The fabricated gold nanorods were found to have an elongated, rod-like shape. The major axis length of the gold nanorods was 69.9 ± 5.8 nm, the minor axis length was 13.2 ± 1.8 nm, and the aspect ratio was 5.3.
[0067] Next, the synthesized gold nanorods were modified with folic acid-modified gelatin. Folic acid-modified gelatin was synthesized by reacting folic acid with gelatin. 400 mg of folic acid was dissolved in 10 mL of dimethyl sulfoxide (DMSO). 374 mg of N,N'-dicyclohexylcarbodiimide (DCC) was dissolved in 10 mL of DMSO. 84 mg of N-hydroxysuccinimide (NHS) was dissolved in 20 mL of DMSO.
[0068] The DMSO solutions of folic acid, DCC, and NHS were mixed and reacted at room temperature for 6 hours. Next, the mixture was centrifuged at 12,000 rpm for 30 minutes to remove N,N'-dicyclohexylurea. Then, the NHS folic acid dissolved in the supernatant was precipitated in a mixed solvent of diethyl ether and acetone (70:30, vol / vol) at -20°C and centrifuged at 12,000 rpm for 10 minutes at -2°C.
[0069] Furthermore, the precipitate obtained by centrifugation was dissolved in DMSO solution, precipitated in a mixed solvent of diethyl ether and acetone, and purified by repeating this centrifugation process twice. After that, the NHS folate was dried under vacuum. Subsequently, 120 mg of NHS folate was dissolved again in 12 mL of DMSO. 700 mg of gelatin was dissolved in 70 mL of sodium carbonate buffer. The DMSO solution of NHS folate was added to the gelatin and sodium carbonate buffer and reacted overnight at room temperature with stirring.
[0070] Subsequently, the mixed solution was sequentially dialyzed using a dialysis bag with a molecular weight cutoff of 3.5 kDa, using mixed solvents of DMSO and water in volume ratios of 80 / 20, 70 / 30, and 60 / 40, and pure water, to remove unreacted folic acid NHS and purify the folic acid-modified gelatin.
[0071] After freeze-drying, folate-modified gelatin was obtained. The synthesized folate-modified gelatin was dissolved in Milli-Q water to prepare a 0.5% (wt / vol) aqueous solution of folate-modified gelatin. The synthesized gold nanorods were placed in the 0.5% (wt / vol) aqueous solution of folate-modified gelatin and stirred at room temperature for 24 hours to allow the folate-modified gelatin to coat the gold nanorods. Subsequently, the folate-modified gelatin gold nanorods (hereinafter simply referred to as gold nanorods for simplicity) were collected by centrifugation and washed with Milli-Q water.
[0072] <Anticancer drug-encapsulated liposomes> As anticancer drug-encapsulating liposomes, we prepared liposomes containing doxorubicin.
[0073] To create liposomes, 1,2-dihexadecanoyl-sn-glycero-3-phosphocholine (DPPC), cholesterol, and 1,2-distearoyl-sn-glycero-3-phosphoethanolamine-N-[amino(polyethylene glycol)-2000] (abbreviated as DSPE-PEG2000-NH2) were used, and doxorubicin was encapsulated within them using the Bangum method.
[0074] I will explain in detail. First, 5 mL of chloroform was added to a 50 mL round-bottom flask, rinsed to remove the chloroform, and the flask was dried before the lipid solution was added. The lipid solution was a mixture of 1200 μL of DPPC (5 mg / mL), 160 μL of cholesterol (5 mg / mL), and 640 μL of DSPE-PEG2000-NH2 (5 mg / mL). A chloroform-methanol mixed solvent was used as the solvent. The volume of the mixed solution was 2 mL, with a volume ratio of chloroform to methanol of 9:1 and a molar ratio of DPPC, cholesterol, and DSPE-PEG2000-NH2 of 7:2:1.
[0075] Next, the round-bottom flask was connected to a rotary evaporator and immersed in a 45°C water bath. The chloroform / methanol mixed solvent was gradually evaporated under vacuum and rotation. After all of the mixed solvent was removed, a thin film was formed. To completely remove the mixed solvent, the flask was dried overnight in a vacuum dryer, and a lipid film of DPPC, cholesterol, and DSPE-PEG2000-NH2 was formed on the inner surface of the flask.
[0076] Finally, doxorubicin is dissolved in phosphate buffer solution, and the concentration is 1 mg / mL (= 1 mg / cm³). 3 A doxorubicin solution was prepared. 1 mL of the prepared doxorubicin solution was added to a flask with a lipid membrane formed on it, and the entire lipid membrane was moistened at room temperature for 30 minutes. Then, the flask with the moistened lipid membrane was sonicated for 30 minutes while being warmed in a 60°C water bath. After that, the sonicated solution was extruded 21 times through a polycarbonate membrane with a pore size of 200 nm at 60°C.
[0077] The extruded liposomes were centrifuged at 20,000 rpm for 15 minutes, washed twice with phosphate buffer solution, resuspended in phosphate buffer solution, and stored at 4°C. In this way, doxorubicin-encapsulated liposomes were obtained. Thus, by employing the Bangham method, when an aqueous solution of an anticancer drug is added to the lipid membrane and hydrated, the lipids self-assemble, and liposomes encapsulating doxorubicin are produced. The particle size of the produced doxorubicin-encapsulated liposomes was measured by dynamic light scattering.
[0078] Figure 2 shows the dynamic light scattering grain size distribution of the prepared doxorubicin-encapsulated liposomes.
[0079] As shown in Figure 2, the average particle size of liposomes encapsulating doxorubicin was 221.3 ± 85.6 nm. Furthermore, when the amount of doxorubicin encapsulated in the liposomes was measured using a fluorescence spectrometer, the encapsulation efficiency of doxorubicin into the liposomes was 56.5 ± 3.8%.
[0080] [Example 1] In Example 1, a composite porous material was prepared using gold nanorods (gold nanorods modified with folic acid-modified gelatin) as photothermal conversion nanoparticles, doxorubicin-encapsulated liposomes as anticancer drug-encapsulating liposomes, and folic acid-modified gelatin and polyglutamic acid as bioabsorbable polymers.
[0081] First, gold nanorods were mixed with folate-modified gelatin and polyglutamic acid as bioabsorbable polymers to create a porous material of gold nanorods / folate-modified gelatin / polyglutamic acid (porosity formation process).
[0082] To control the porous structure, pre-prepared ice microparticles were used. The ice microparticles were prepared by spraying Milli-Q water onto liquid nitrogen. The prepared ice microparticles were sieved through mesh sieves with mesh sizes of 425 μm and 500 μm to obtain ice microparticles with particle diameters in the range of 425 μm to 500 μm.
[0083] The folic acid-modified gelatin used in the preparation of the gold nanorods was dissolved in a 35% aqueous acetic acid solution to adjust the concentration of the folic acid-modified gelatin to 8%. The gold nanorods were added to the aqueous acetic acid solution of folic acid-modified gelatin and mixed to prepare a mixture of folic acid-modified gelatin and gold nanorods. The folic acid-modified gelatin attached to the gold nanorods was maintained even in the mixture.
[0084] Furthermore, polyglutamic acid was dissolved in a 35% aqueous acetic acid solution to adjust the concentration of polyglutamic acid to 0.8%. The same volume of gold nanorod / folate-modified gelatin mixture was mixed with the aqueous acetic acid solution of polyglutamic acid to prepare a mixture of gold nanorod / folate-modified gelatin / polyglutamic acid.
[0085] In the mixture of gold nanorods, folic acid-modified gelatin, and polyglutamic acid, the final concentration of gold nanorods is 2 mM (i.e., calculated using the atomic weight of gold, 197, this is 394 μg / cm³). 3 The final concentration of folate-modified gelatin was 4 (w / v)%, and the final concentration of polyglutamic acid was 0.4 (w / v). When the weight ratio of gold nanorods to folate-modified gelatin and polyglutamic acid was calculated, the weight of gold nanorods per 1 mL of the mixture was 394 × 10⁶. -6 Since the total weight of folate-modified gelatin (0.04g) and polyglutamic acid (0.004g) was 0.044g, the weight ratio (gold nanorods / folate-modified gelatin and polyglutamic acid) was 0.009.
[0086] Furthermore, in a low-temperature chamber at -4°C, ice nanoparticles with a particle size of 425 μm to 500 μm were mixed with a mixture of gold nanorods / folate-modified gelatin / polyglutamic acid in a weight-to-volume ratio of 7:3. The mixture was thoroughly mixed to ensure that the ice nanoparticles were uniformly distributed in the solution. This mixture was frozen at -20°C for 12 hours and at -80°C for 4 hours, and then freeze-dried. After washing the freeze-dried gold nanorods / folate-modified gelatin / polyglutamic acid with ethanol, the cross-linking reaction was carried out sequentially in the following three steps.
[0087] First, the lyophilized material was washed with 99.5% ethanol (30 minutes x 10 times). In the crosslinking reaction process, in order to prevent gelatin from dissolving while increasing the efficiency of the crosslinking reaction, three types of ethanol aqueous solutions with progressively lower ethanol concentrations (ethanol / water (v / v) = 95 / 5, 90 / 10, 85 / 15) were used. In the first crosslinking reaction step, 0.03 g of 2-morpholinoethanesulfonic acid (MES) was added to 30 mL of ethanol / water (95 / 5, v / v) while stirring, and the mixture was stirred for 1 to 2 hours. To this MES solution, 0.288 g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC, final concentration 50 mM) and 0.069 g of N-hydroxysuccinimide (NHS, final concentration 20 mM) were added and stirred at room temperature for 10 minutes to prepare the first crosslinking reaction solution. The first stage of the crosslinking reaction was carried out by immersing the gold nanorods / folic acid-modified gelatin / polyglutamic acid freeze-dried material in this first stage crosslinking reaction solution at room temperature for 8 hours.
[0088] In the second crosslinking reaction step, 0.03 g of MES was added to 30 mL of ethanol / water (90 / 10, v / v) while stirring. To this MES solution, 0.288 g of EDC and 0.069 g of NHS were added and stirred for 10 minutes to prepare the second crosslinking reaction solution. The gold nanorods / folate-modified gelatin / polyglutamic acid freeze-dried material from the first crosslinking reaction was immersed in this second crosslinking reaction solution at room temperature for 8 hours to carry out the second crosslinking reaction.
[0089] In the third crosslinking reaction step, 0.03 g of MES was added to 30 mL of ethanol / water (85 / 15, v / v) while stirring, and the mixture was stirred for 1 to 2 hours. To this MES solution, 0.288 g of EDC and 0.069 g of NHS were added and stirred for 10 minutes to prepare the third crosslinking reaction solution. The gold nanorods / folate-modified gelatin / polyglutamic acid freeze-dried material from the second crosslinking reaction was immersed in this third crosslinking reaction solution at room temperature for 8 hours to carry out the third crosslinking reaction. The gold nanorods / folate-modified gelatin / polyglutamic acid freeze-dried material from the final crosslinking reaction was immersed in pure water at room temperature for 1 hour, and this was repeated 8 times as one washing cycle. In this way, a porous material of folate-modified gold nanorods, polyglutamic acid, and folate-modified gelatin was obtained. After freeze-drying this porous material, it was cut into discs with a diameter of 6 mm and a thickness of 1 mm.
[0090] Next, doxorubicin-encapsulated liposomes were introduced into a porous material of gold nanorods / folate-modified gelatin / polyglutamic acid (introduction step) to create a composite porous material of gold nanorods / folate-modified gelatin / polyglutamic acid / doxorubicin-encapsulated liposomes.
[0091] Porous materials of gold nanorods / folate-modified gelatin / polyglutamic acid were immersed in a phosphate buffer solution containing 50 mM EDC and 20 mM NHS at room temperature for 6 hours to further activate the carboxyl groups. Subsequently, the porous materials were washed three times with phosphate buffer to remove excess EDC / NHS, and any remaining phosphate buffer solution on the porous materials was absorbed with paper.
[0092] Next, 30 μL of doxorubicin-encapsulated liposome solution, prepared to have a doxorubicin concentration of 1 mg / mL, was added to the aforementioned carboxyl-activated gold nanorod / folate-modified gelatin / polyglutamic acid composite porous material (cut into discs with a diameter of 6 mm and a thickness of 1 mm), and incubated at room temperature with shaking for 12 hours. This allowed condensation polymerization to proceed between the carboxyl groups of gelatin and polyglutamic acid and the surface amino groups of the liposomes, resulting in chemical bonding.
[0093] Subsequently, the material was washed three times with phosphate buffer to prepare a composite porous material of gold nanorods / folate-modified gelatin / polyglutamic acid / doxorubicin-encapsulated liposomes. The prepared composite porous material of gold nanorods / folate-modified gelatin / polyglutamic acid / doxorubicin-encapsulated liposomes (composite porous material of Example 1) was stored at 4°C. Furthermore, the amount of doxorubicin introduced into this composite porous material was measured using a fluorescence spectrometer, and the efficiency of doxorubicin introduction into the composite porous material was found to be 57.4 ± 6.3%.
[0094] <Observation and Properties of Composite Porous Materials> The porous structure of the composite porous material obtained in this manner in Example 1 was observed using an electron microscope (SEM). The results are shown in Figure 3.
[0095] <Heat-generating effect> Next, 30 μL of Milli-Q water was impregnated into the composite porous material of Example 1 (a disc-shaped material with a diameter of 6 mm and a thickness of 1 mm), and the wavelength was 805 nm and the intensity was 1.0 W / cm². -2 , 1.6Wcm -2 , 2.0Wcm -2 Near-infrared light (near-infrared laser light) was irradiated onto each sample for 10 minutes. During this time, the sample temperature was measured every 30 seconds using a digital thermometer to investigate the heat generation effect. The results are shown in Figure 6.
[0096] <Sustained-release effect of anticancer drugs> The composite porous material from Example 1 (disk-shaped, 6 mm in diameter and 1 mm thick) was immersed in 500 μL of phosphate buffer solution at 37°C. After 24 hours, the intensity was 1.0 W / cm². 2 and 1.6 W / cm² 2The composite porous material was irradiated with near-infrared light for 10 minutes. Thereafter, every time it was incubated at 37 °C for 24 hours, the same irradiation as above was repeated. Before the near-infrared light irradiation and after each irradiation, 100 μL of phosphate buffer solution was collected, and 100 μL of phosphate buffer solution was replenished at that time. The amount of doxorubicin released in the collected phosphate buffer solution was measured, and the cumulative sustained release rate of doxorubicin was calculated. Also, samples were collected at the same time points for the amount of doxorubicin released from the composite porous material in phosphate buffer solution (37 °C), measured in the same manner, and the cumulative sustained release rate was calculated. The results are shown in Fig. 9.
[0097] <In vitro killing effect: Fluorescence microscopy observation> Human breast cancer cell line (MDA-MB-231-Luc) was seeded at 1 × 10 5 on the upper surface of the composite porous material (disk-shaped with a diameter of 6 mm and a thickness of 1 mm) of Example 1 and cultured for 6 hours. Thereafter, the disk-shaped composite porous material was turned over, and human breast cancer cell line (MDA-MB-231-Luc) was further seeded at 1 × 10 5 and cultured for 6 hours. After the culture, the disk-shaped composite porous material seeded with cells was placed in a Transwell insert and further cultured for 12 hours. Thereafter, the disk-shaped composite porous material seeded with cells was taken out from the Transwell insert and irradiated with near-infrared light at wavelengths of 805 nm and intensities of 1.0 W cm -2 and 1.6 W cm -2 for 10 minutes each, then returned to the Transwell insert and further cultured for 1 day. The live and dead cells of the composite porous material after 1-day culture were cultured in serum-free medium containing calcein-AM and propidium iodide for 15 minutes for staining. The results of fluorescence microscopy observation of the stained live and dead cells are shown in Fig. 10.
[0098] <In vitro killing effect: WST-1 method> Human breast cancer cell line (MDA-MB-231-Luc) was seeded at 1 × 10 5Seeded and cultured for 6 hours. Then, the disk-shaped composite porous material was turned over, and the human breast cancer cell line (MDA-MB-231-Luc) was seeded at 1×10 5 cells and cultured for 6 hours. After culturing, the disk-shaped composite porous material seeded with cells was placed in a Transwell insert and further cultured for 12 hours. Then, the disk-shaped composite porous material seeded with cells was taken out from the Transwell insert, and near-infrared light with a wavelength of 805 nm and intensities of 1.0 W / cm -2 and 1.6 W / cm -2 was irradiated for 10 minutes each, and then cultured for 1 day and 3 days. The cell viability in the composite porous material after culturing for 1 day and 3 days was measured using the known WST-1 method. The cell viability in the composite porous material is shown in FIGS. 13 and 14.
[0099] <In vivo photothermal killing effect> On the upper surface of the composite porous material (disk-shaped with a diameter of 6 mm and a thickness of 1 mm) of Example 1, the human breast cancer cell line (MDA-MB-231-Luc) was seeded at 1×10 5 cells and cultured for 6 hours. Then, the disk-shaped composite porous material was turned over, and the human breast cancer cell line (MDA-MB-231-Luc) was seeded at 1×10 5 cells and cultured for 6 hours. Then, the disk-shaped composite porous material seeded with cells was further cultured for 12 hours.
[0100] Here, a ring-shaped frame made of a porous material of folic acid-modified gelatin and polyglutamic acid (that is, without gold nanorods and doxorubicin-encapsulated liposomes) was prepared. The size of the ring-shaped frame was 1 mm in thickness, 6 mm in inner diameter, and 10 mm in outer shape. The method for preparing the porous material of folic acid-modified gelatin / polyglutamic acid was the same as that in Example 1, except that gold nanorods and doxorubicin-encapsulated liposomes were not used. 1×10 5 MDA-MB-231-Luc cells were seeded on both sides of the ring-shaped frame of the folic acid-modified gelatin / polyglutamic acid porous material (2×10 5Individual cancer cells were cultured for 6 hours after each cell seeding. Subsequently, the cells were cultured for a further 12 hours on a disc-shaped porous composite material on which they had been seeded. Then, the disc-shaped porous composite material was placed in the hollow space of a ring-shaped frame on which the cells had been seeded, and this constituted one culture set.
[0101] The culture was implanted subcutaneously into the backs of nude mice under general anesthesia, with one set per mouse. One day later, near-infrared light (805 nm, intensity 1.6 W cm) was applied to the skin at the implantation site. -2 The mice were irradiated with near-infrared light for 10 minutes. One day later, they were irradiated again under the same conditions for a total of two times. Before near-infrared light irradiation, and 1, 3, 7, 10, and 14 days after the two irradiations, D-luciferin was injected into the peritoneal cavity of the mice, and in vivo chemiluminescence imaging was performed 10 minutes later. The results are shown in Figure 15.
[0102] [Comparative Example 1] In Comparative Example 1, a composite porous material (control) was prepared using folic acid-modified gold nanorods as photothermal conversion nanoparticles and folic acid-modified gelatin and polyglutamic acid as bioabsorbable polymers.
[0103] The preparation conditions were the same as in Example 1, except that doxorubicin-encapsulated liposomes were not added as anticancer drug-encapsulating liposomes. The composite porous material of gold nanorods / folate-modified gelatin / polyglutamic acid obtained in this way (composite porous material of Comparative Example 1) was stored at 4°C.
[0104] The composite porous material of Comparative Example 1, obtained in this manner, was observed using SEM in the same manner as in Example 1, and its heat-generating effect, in vitro toxic effect (fluorescence microscopy and WST-1 method), and in vivo photothermal toxic effect were investigated. These results are shown in Figures 4, 7, 11, 13, 14, and 16.
[0105] [Comparative Example 2] In Comparative Example 2, a composite porous material (control) was prepared using doxorubicin-encapsulated liposomes as anticancer drug-encapsulating liposomes and folic acid-modified gelatin and polyglutamic acid as bioabsorbable polymers.
[0106] The preparation conditions were the same as in Example 1, except that folic acid-modified gold nanorods were not added as photothermal conversion nanoparticles. The resulting composite porous material of folic acid-modified gelatin / polyglutamic acid / doxorubicin-encapsulated liposomes (composite porous material of Comparative Example 2) was stored at 4°C.
[0107] The composite porous material of Comparative Example 1, obtained in this manner, was observed using SEM in the same manner as in Example 1, and its heat-generating effect, in vitro toxic effect (fluorescence microscopy and WST-1 method), and in vivo photothermal toxic effect were investigated. These results are shown in Figures 5, 8, 12-14, and 17.
[0108] The composite porous materials of Example 1 and Comparative Examples 1-2 described above were observed using SEM, and the results of the heat generation effect, sustained release effect of anticancer drugs, in vitro killing effect (fluorescence microscopy and WST-1 method), and in vivo photothermal killing effect are summarized and explained. For clarity, Table 1 shows the constituent components of the composite porous materials of Example 1 and Comparative Examples 1-2.
[0109] [Table 1]
[0110] Figure 3 shows an SEM observation of the interior of the composite porous material of Example 1. Figure 4 shows an SEM observation of the interior of the composite porous material of Comparative Example 1. Figure 5 shows an SEM observation of the interior of the composite porous material of Comparative Example 2.
[0111] As shown in Figure 3, the composite porous material of Example 1 was found to be porous with pore sizes ranging from 10 μm to 500 μm. These pore sizes reflected the size of the ice particles used as a pore-forming agent. As shown in Figures 4 and 5, the composite porous materials of Comparative Examples 1 and 2 exhibited similar characteristics. From these findings, it was concluded that the pore structure of porous materials can be controlled by the use of a pore-forming agent.
[0112] The porosity of the composite porous material in Example 1 can be estimated as follows. For example, suppose 3 mL of the mixed solution is used. In this case, the weight of folic acid-modified gelatin is 3 mL × 0.04 g / mL = 0.12 g, and the weight of polyglutamic acid is 3 mL × 0.004 g / mL = 0.012 g. Since the total amount of 10 g is 7 g of ice particles and 3 g of folic acid-modified gelatin solution, the porosity is (10 - 0.12 - 0.012) / 10 × 100 = 98.7, which is approximately 99%. Here, 1. The specific gravity of each component is 1. 2. Volume changes due to freezing can be ignored. 3. The contribution of gold nanoparticles and doxorubicin-encapsulated liposomes to the volume is negligible. Let us assume that this is the case.
[0113] Figure 6 shows the temperature change when the composite porous material of Example 1 is irradiated with near-infrared light. Figure 7 shows the temperature change when near-infrared light is irradiated onto the composite porous material of Comparative Example 1. Figure 8 shows the temperature change when near-infrared light is irradiated onto the composite porous material of Comparative Example 2.
[0114] As shown in Figures 6 and 7, the composite porous materials of Example 1 and Comparative Example 1 both showed an increase in temperature with increasing irradiation time and intensity of near-infrared light, confirming a heat-generating effect. Since both of these composite porous materials contain gold nanorods, it is thought that the temperature rise was due to the photothermal conversion effect caused by near-infrared light irradiation. Furthermore, since the heat-generating effect of the composite porous material of Example 1 was similar to that of Comparative Example 1, it was found that the heat-generating effect is not inhibited even if anticancer drug-encapsulating liposomes are present. On the other hand, as shown in Figure 8, the temperature rise of the composite porous material of Comparative Example 2 was only slight when irradiated with near-infrared light compared to that of Example 1 and Comparative Example 1.
[0115] From the above, it was confirmed that the composite porous material of Example 1 can be implanted in the body and generates heat when irradiated with near-infrared light from outside the body, making it applicable to hyperthermia therapy for cancer.
[0116] Figure 9 shows the accumulation and sustained release curve of doxorubicin when the composite porous material of Example 1 is irradiated with near-infrared light.
[0117] In Figure 9, the time point indicated by the arrow corresponds to an intensity of 1.0 W / cm². 2 and 1.6 W / cm² 2 This is the start time of near-infrared light irradiation. Figure 9 also shows the accumulation and sustained release curve of doxorubicin in a phosphate buffer solution at 37°C.
[0118] According to the accumulation and sustained-release curve in a phosphate buffer solution at 37°C shown in Figure 9, the accumulation and sustained-release rate of doxorubicin increased slowly over time. In contrast, when irradiated with near-infrared light every 10 minutes, the accumulation and sustained-release rate increased rapidly with each irradiation. (Intensity: 1.0 W / cm²) 2 and 1.6 W / cm² 2 The accumulation and release rates after 10 minutes of irradiation with near-infrared light were similar.
[0119] Although not shown in the figures, in the case of Comparative Example 2, a composite porous material containing only doxorubicin-encapsulated liposomes and no gold nanorods, the accumulation and sustained release rate remained unchanged from that of a phosphate buffer solution at 37°C, even after irradiation with near-infrared light.
[0120] These results indicate that a composite porous material containing both gold nanorods and doxorubicin-encapsulated liposomes can slowly release doxorubicin at a body temperature of approximately 37°C, and that near-infrared light irradiation can accelerate the release of doxorubicin.
[0121] From the above, it was shown that the composite porous material of Example 1 can be implanted in a living organism, and by controlling the irradiation conditions of near-infrared light from outside the body (irradiation time, intensity, etc.), the sustained release rate of anticancer drugs can be controlled by utilizing the heat generated by photothermal conversion nanoparticles in addition to body temperature, making it applicable to cancer chemotherapy.
[0122] Figure 10 shows a fluorescence micrograph of the composite porous material from Example 1, in which human cancer cell lines were cultured after infrared light irradiation (cultivated for 1 day). Figure 11 shows a fluorescence micrograph of a composite porous material of Comparative Example 1, in which human cancer cell lines were cultured after infrared light irradiation (cultivated for 1 day). Figure 12 shows a fluorescence micrograph of a composite porous material of Comparative Example 2, in which human cancer cell lines were cultured after infrared light irradiation (cultivated for 1 day).
[0123] In Figures 10 to 12, the left and right figures represent an intensity of 1.0 W / cm², respectively. 2 and 1.6 W / cm² 2 The figure shows the results of irradiating a composite porous material with near-infrared light for 10 minutes and then culturing it for 24 hours. Note that although the figure is shown in grayscale, in reality, living cells are shown with green fluorescence and dead cells with red fluorescence.
[0124] According to the left diagram in Figures 10 and 11, the composite porous materials of Example 1 and Comparative Example 1 were exposed to near-infrared light (intensity: 1.0 Wcm²). -2 When irradiated with (), some red fluorescence indicating dead cells was observed in addition to green fluorescence indicating living cells, indicating that some breast cancer cells were killed. As shown in the right-hand figures of Figures 10 and 11, the composite porous materials of Example 1 and Comparative Example 1 were irradiated with near-infrared light (intensity: 1.6 Wcm²) at an even higher intensity. -2 When irradiated with ), most cells exhibited red fluorescence, and many breast cancer cells were killed.
[0125] On the other hand, as shown in Figure 12, when the composite porous material of Comparative Example 2 was irradiated with near-infrared light, most cells showed green fluorescence regardless of the intensity, and no killing effect on mammary cancer cells was observed. Naturally, there was no thermal effect from near-infrared light irradiation in the composite porous material of Comparative Example 2, and in addition, it is thought that the cancer cell killing effect of doxorubicin released from liposomes had not yet appeared after one day of culture.
[0126] Figure 13 shows the cell viability in composite porous materials of Example 1 and Comparative Examples 1-2, in which human cancer cell lines were cultured after infrared light irradiation (cultured for 1 day). Figure 14 shows the cell viability in composite porous materials of Example 1 and Comparative Examples 1-2, in which human cancer cell lines were cultured after infrared light irradiation (3-day culture).
[0127] As shown in Figure 13, when irradiated with near-infrared light and cultured for one day, the cell viability of the composite porous materials in Example 1 and Comparative Example 1 was lower than that of the composite porous material in Comparative Example 2. In particular, in the composite porous materials of Example 1 and Comparative Example 1, when the strength was 1.6 Wcm, -2 The cell viability when irradiated with near-infrared light is 1.0 W / cm². -2 The reduction was significantly greater compared to the result obtained when near-infrared light was irradiated. This result is consistent with the results shown in Figures 10 and 11, and indicates the heat generation effect by photothermal conversion nanoparticles.
[0128] On the other hand, Figure 14 shows that the results differed from those in Figure 13 when cells were irradiated with near-infrared light and cultured for 3 days. The activity of cells cultured for 3 days after near-infrared light irradiation in the composite porous material of Example 1 was dramatically lower than the activity of cells cultured for 1 day (Figure 13). However, the activity of cells cultured for 3 days after near-infrared light irradiation in the composite porous material of Comparative Example 1 was higher than the activity of cells cultured for 1 day. The activity of cells cultured for 1 day after near-infrared light irradiation in the composite porous material of Comparative Example 2 decreased slightly, but the activity of cells cultured for 3 days decreased significantly. This suggests that in the composite porous material of Comparative Example 1, near-infrared irradiation killed some cancer cells, and then the few surviving cancer cells proliferated after 3 days of culture. On the other hand, in the composite porous material of Comparative Example 2, there was no heat-generating effect even with near-infrared irradiation, so the activity of cancer cells hardly changed even with near-infrared irradiation. However, after 3 days of culture, doxorubicin was slightly released, killing some cancer cells, and the activity of cancer cells decreased significantly.
[0129] In contrast, in the composite porous material of Example 1, the activity of cancer cells decreased significantly one day after near-infrared irradiation, and the activity of cancer cells decreased even more significantly after three days of culture. This suggests that the breast cancer cells were killed by the synergistic effect of hyperthermia therapy using gold nanorods in the composite porous material of Example 1 and chemotherapy by sustained-release doxorubicin.
[0130] The dramatic reduction in cell viability in the composite porous material of Example 1 due to hyperthermia and chemotherapy is not simply the sum of the effects of hyperthermia in the composite porous material of Comparative Example 1 and the effects of chemotherapy in the composite porous material of Comparative Example 2. Heating with near-infrared light weakens cancer cells, and these weakened cancer cells become more susceptible to being killed by sustained-release anticancer drugs. Furthermore, cancer cells weakened by anticancer drugs become more susceptible to being killed by further heating with near-infrared light. In addition, because it is a porous material, cancer cells can be allowed to penetrate and remain within the porous structure, thus achieving such synergistic effects and efficiently killing cancer cells.
[0131] Figure 15 shows an in vivo chemiluminescence image of mice transplanted with the composite porous material from Example 1, in which human cancer cell lines were cultured after infrared light irradiation. Figure 16 shows an in vivo chemiluminescence image of mice transplanted with the composite porous material of Comparative Example 1, which was a human cancer cell line cultured after infrared light irradiation. Figure 17 shows an in vivo chemiluminescence image of mice transplanted with the composite porous material of Comparative Example 2, which was cultured using human cancer cell lines after infrared light irradiation.
[0132] Figure 15 shows in vivo chemiluminescence images of cancer cells cultured in the composite porous material of Example 1 before near-infrared light irradiation, and 1, 3, 7, 10, and 14 days after two irradiations. Figure 16 shows in vivo chemiluminescence images of cancer cells cultured in the composite porous material of Comparative Example 1 before near-infrared light irradiation, and 1 and 14 days after two irradiations. Figure 17 shows in vivo chemiluminescence images of cancer cells cultured in the composite porous material of Comparative Example 2 before near-infrared light irradiation, and 1 and 14 days after two irradiations.
[0133] Figures 15-17 are shown in grayscale, but in reality, the colors change in the order of red, yellow, green, and blue, from areas with a high concentration of cancer cells to areas with a low concentration. Areas that are shown particularly darkly can be considered to be areas where cancer cells are present.
[0134] According to Figures 15-17, before near-infrared light irradiation, luminescent regions indicating the presence of cancer cells were observed at the implantation site in mice for all composite porous materials. As shown in Figure 15, in the composite porous material of Example 1, one day after near-infrared light irradiation, the luminescent region in the central area of the implantation site disappeared, and luminescence was detected around the implantation site. This is thought to be because the composite porous material of Example 1 generated heat upon near-infrared light irradiation, and the mammary cancer cells in the composite porous material disk were killed by the thermal effect, resulting in the elimination of luminescence as the mammary cancer cells in the central area of the implantation site died. However, mammary cancer cells survived in the ring-shaped frame (which did not contain gold nanoparticles or doxorubicin) on which the composite porous material of Example 1 was supported, and luminescence was detected around the implantation site. However, three days after near-infrared light irradiation, the luminescent region around the irradiation site became even smaller, and after seven days, the luminescent region became barely visible. After ten days, it had completely disappeared, and after fourteen days, it remained gone. This indicates that doxorubicin was released from the composite porous material disk, killing the surrounding breast cancer cells.
[0135] As shown in Figure 16, in the composite porous material of Comparative Example 1, the luminescent region in the central area of the implantation site disappeared one day after near-infrared light irradiation, and luminescence was detected around the implantation site. This is thought to be because the composite porous material of Comparative Example 1 generated heat upon near-infrared light irradiation, and the breast cancer cells in the composite porous material disk were killed by the thermal effect, resulting in the elimination of luminescence in the central area of the implantation site. However, breast cancer cells survived in the ring-shaped frame on which the composite porous material of Comparative Example 1 was supported, and luminescence was detected around the implantation site. The remaining cancer cells were still alive 14 days after near-infrared light irradiation.
[0136] As shown in Figure 17, in the composite porous material of Comparative Example 2, some cancer cells survived one day after near-infrared light irradiation, and a small number of cancer cells were still detected after 14 days. This is thought to be because the cancer cells were killed by doxorubicin, which was slowly released from the composite porous material of Comparative Example 2 by body temperature.
[0137] These results demonstrate that a composite porous material containing a bioabsorbable polymer, photothermal conversion nanoparticles that generate heat upon near-infrared light irradiation, and liposomes containing an anticancer drug can effectively kill cancer cells through a synergistic effect of hyperthermia therapy induced by near-infrared light irradiation and chemotherapy with an anticancer drug that is slowly released by body temperature and heat generation. [Industrial applicability]
[0138] The composite porous material of the present invention, when transplanted to or covering the site of cancerous tissue excision, can not only kill cancerous tissue and cancer cells by irradiation with near-infrared light, but also allow cancer cells to enter the pores, thus efficiently killing cancer cells. Moreover, because the photothermal conversion nanoparticles are supported on the porous material, rapid diffusion of the photothermal conversion nanoparticles, which reduces photothermal efficiency, is prevented, making it possible to repeatedly heat the site of cancerous tissue excision or cancerous tissue locally. Furthermore, because anticancer drug-encapsulating liposomes are supported on the porous material, the sustained release rate of the anticancer drug can be controlled by irradiation with near-infrared light. Using the composite porous material of the present invention helps to prevent cancer recurrence while minimizing the decline in tissue and organ function after cancer treatment. Therefore, the composite porous material of the present invention is extremely effective in the treatment of cancer.
Claims
1. A composite porous material containing a bioabsorbable polymer, photothermal conversion nanoparticles that generate heat when irradiated with near-infrared light, and liposomes encapsulating an anticancer drug.
2. The composite porous material according to claim 1 , wherein the photothermal conversion nanoparticles are at least one selected from the group consisting of gold nanoparticles and black phosphorus nanosheets.
3. The composite porous material according to claim 2 , wherein the gold nanoparticles are rod-shaped gold nanorods or star-shaped gold nanostars.
4. The gold nanorod has a long axis length in the range of 20 nm to 500 nm, a short axis length in the range of 1 nm to 80 nm, and an aspect ratio (long axis length / short axis length) in the range of 2 to 50; The composite porous material of claim 3, wherein the gold nanostars have a particle size in the range of 20 nm to 500 nm.
5. The thickness of the black phosphorus nanosheet is in the range of 1 nm to 1,000 nm, and the area is 100 nm 2 ~100,000μm 2 The composite porous material according to claim 2, wherein the surface area of the porous material is in the range of
6. The composite porous material according to claim 1 , wherein the anticancer drug is slowly released from the liposomes by body temperature, and the release rate is increased by heat generation of the photothermal conversion nanoparticles.
7. The composite porous material according to claim 1, wherein the anticancer drug is one or more selected from the group consisting of doxorubicin, paclitaxel, docetaxel hydrate, methotrexate, fluorouracil, tegafur, tegafur-uracil, carmofur, doxifluridine, capecitabine, tegafur-gimeracil-oteracil potassium, mitomycin C, captothecin, and cisplatin.
8. The composite porous material according to claim 1, wherein the liposome is composed of 1,2-dihexadecanoyl-sn-glycero-3-phosphocholine (abbreviated as DPPC), cholesterol, and 1,2-distearoyl-sn-glycero-3-phosphoethanolamine (abbreviated as DSPE) modified with polyethylene glycol.
9. The composite porous material according to claim 1, wherein the bioabsorbable polymer is one or more selected from the group consisting of gelatin, collagen, fibrin, hyaluronic acid, polyglutamic acid, chondroitin sulfate, alginic acid, polylactic acid, polyglycolic acid, copolymers of lactic acid and glycolic acid, poly(ε-caprolactone), poly(glycerol sebacic acid), and copolymers thereof.
10. The composite porous material according to claim 1 , wherein the bioabsorbable polymer is a bioabsorbable synthetic polymer sponge or a bioabsorbable synthetic polymer mesh body.
11. The composite porous material according to claim 10 , wherein the bioabsorbable synthetic polymer mesh body is a woven fabric, a woven cloth, or a nonwoven fabric.
12. The composite porous material according to claim 1, having pores with a pore size in the range of 0.1 to 1200 μm.
13. The composite porous material of claim 1 , wherein the bioabsorbable polymer is crosslinked.
14. The concentration of the photothermal conversion nanoparticles is 1 μg / cm 3 4,000 μg / cm or more 3 2. The composite porous material of claim 1, wherein the porous material has a molecular weight of 1000 or more.
15. The composite porous material according to claim 1, wherein the weight ratio of the photothermal conversion nanoparticles to the bioabsorbable polymer (photothermal conversion nanoparticles / bioabsorbable polymer) is in the range of 0.0005 to 0.
5.
16. The final concentration of the anticancer drug released by the liposome is 0.01 mg / cm 3 100mg / cm or more 3 2. The composite porous material of claim 1, wherein the porous material has a molecular weight of 1000 or more.
17. The composite porous material according to claim 1, which is embedded in a site where cancer tissue has been removed by surgical operation or which directly covers the cancer tissue and generates heat when irradiated with near-infrared light from the outside, thereby killing internal or surrounding cancer cells.
18. Mixing photothermal conversion nanoparticles and a bioabsorbable polymer to make the mixture porous; introducing liposomes encapsulating an anticancer drug into the porous material of the photothermal conversion nanoparticles and the bioabsorbable polymer obtained by the porosification; The method for producing the composite porous material according to any one of claims 1 to 17, comprising:
19. The method for producing a composite porous material according to claim 18 , wherein the step of making the material porous comprises freeze-drying a mixed solution of the photothermal conversion nanoparticles and the bioabsorbable polymer.
20. The method for producing a composite porous material according to claim 18, wherein the step of making the material porous comprises forming pores using a pore-forming agent.
21. The method for producing a composite porous material according to claim 20, wherein the pore-forming agent is ice.
22. 20. The method of claim 18, further comprising cross-linking the porous material subsequent to said porosifying.
23. The method for producing a composite porous material according to claim 18, wherein the liposome encapsulating the anticancer drug is produced by a method selected from the group consisting of the Bangham method, the cholic acid removal method, the reverse phase evaporation method, the microreactor method, the remote loading method, and the freeze-thaw method.
24. The method for producing a composite porous material according to claim 18 , wherein the introducing step comprises chemically bonding a liposome encapsulating the anticancer drug to the porous material.